Regulatory Exposure of Deceptive Marketing and Its Impact on Firm Value - TIPTON, Martha Myslinski (Institutional Knowledge at Singapore Management University, 2009)
Research linking marketing to financial performance has predominantly focused on how marketing assets and actions add value. The authors argue that it is equally important to understand how marketing decisions can reduce firm value. Prior research has indicated that negative events vary greatly in their indirect costs to the firm. On the basis of established theory and in-depth interviews with practitioners, the authors identify a set of factors that can explain the heterogeneity in the magnitude of indirect costs associated with negative marketing-related events. Specifically, they address how the regulatory exposure of deceptive marketing, which carries no direct cost to the firm, affects shareholder value. Using an event study, the analysis shows that incidents of exposed deceptive marketing are associated with significant, negative abnormal returns amounting to a drop of 1%, which translates into a wealth loss of $86 million for the median-sized firm in the sample. In explaining the variation in magnitude of the impact between events, the authors find that, in general, event characteristics are more significant than firm and brand characteristics. When deception is highly egregious or directed at vulnerable populations, firm value is more negatively affected than when the potential to mislead and harm is not readily verifiable. Furthermore, when the cited product has substantial brand market share, the levels of egregiousness and target audience explain substantially more of the variation in event impact than when brand market share is low. The results are robust to alternative stock-portfolio-based measures of abnormal returns, model specification, heteroskedasticity, and examination of risk. The authors’ framework and analysis have implications for Wall Street executives, Main Street managers, academic researchers, and public policy makers.